5‐Lipoxygenase and cysteinyl leukotriene receptor 1 regulate epidermal growth factor‐induced cell migration through Tiam1 upregulation and Rac1 activation. Issue 3 (28th January 2014) - Magi, Shigeyuki; Takemoto, Yasushi; Kobayashi, Hiroki; Kasamatsu, Masato; Akita, Takahiro; Tanaka, Ayako; Takano, Kei; Tashiro, Etsu; Igarashi, Yasuhiro; Imoto, Masaya
<x xml:space="preserve">Abstract</x> Cell migration is an essential step for tumor metastasis. The small GTPase Rac1 plays an important role in cell migration. Previously, we reported that epidermal growth factor (EGF) induced two waves of Rac1 activation; namely, at 5 min and 12 h after stimulation. A second wave of EGF‐induced Rac1 activation was required for EGF‐induced cell migration, however, the spatiotemporal regulation of the second wave of EGF‐induced Rac1 activation remains largely unclear. In this study, we found that 5‐lipoxygenase (5‐LOX) is activated in the process of EGF‐induced cell migration, and that leukotriene C4 (LTC4) produced by 5‐LOX mediated the second wave of Rac1 activation, as well as cell migration. Furthermore, these effects caused by LTC4 were found to be blocked in the presence of the antagonist of cysteinyl leukotriene receptor 1 (CysLT1). This blockage indicates that LTC4‐mediated CysLT1 signaling regulates the second EGF‐induced wave of Rac1 activation. We also found that 5‐LOX inhibitors, CysLT1 antagonists and the knockdown of CysLT1 inhibited EGF‐induced T cell lymphoma invasion and metastasis‐inducing protein 1 (Tiam1) expression. Tiam1 expression is required for the second wave of EGF‐induced Rac1 activation in A431 cells. Therefore, our results indicate that the 5‐LOX/LTC4/CysLT1 signaling pathway regulates EGF‐induced cell migration by increasing Tiam1 expression, leading to a second wave of Rac1 activation. Thus, CysLT1 may serve as a new molecular target for antimetastatic therapy. In addition, the CysLT1 antagonist, montelukast, which is used clinically for allergy treatment, might have great potential as a novel type of antimetastatic agent.